Optimasi Penggunaan Tanaman Indigofera sebagai Pakan Tambahan Ternak pada Kelompok Tani Jirek Nagari Koto Gadang Kabupaten Agam - Tinda Afriani; Khasrad Khasrad; Reswati Reswati; Mangku Mundana; Mylaufa Asyraf (Warta Pengabdian Andalas, 2024)
Indigofera plants have significant potential to enhance livestock productivity and agricultural sustainability. Community services on using Indigofera plants as supplementary livestock feed have been conducted in the 50 Kota District. This activity aims to increase farmers' knowledge about the benefits of Indigofera plants and their cultivation techniques. The method used involves forming a service team and meeting with farmer groups. The program included information on the benefits of Indigofera plants, cultivation techniques, maintenance, and harvesting. Practical field training was also provided to farmers. The program resulted in a positive response from farmers, who actively participate in the education activities. They understood the potential of Indigofera plants in improving livestock productivity. These plants are nutrient-rich and can be used as a high-quality feed source. They are using Indigofera as supplementary livestock feed, which has a high potential to support healthy and efficient livestock production. This activity is a crucial step in promoting sustainable agriculture and livestock farming.